Method for preparing ferroferric oxide-graphene magnetic heterostructure material and application of ferroferric oxide-graphene magnetic heterostructure material in oriented heat-conducting composite material
The preparation of iron trioxide-graphene magnetic heterostructured materials through calcination reduction method has solved the problem of iron oxide lacking magnetic properties in the prior art, achieved improvement of the magnetic and thermal conductivity of the material, and improved thermal conductivity through magnetic field orientation arrangement.
Patent Information
- Application Number
- CN202411058649.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-02
AI Technical Summary
In the prior art, iron oxide exists in the form of iron trioxide and lacks magnetic properties, which limits its application in thermally conductive composite materials.
The calcination reduction method is used to convert iron trioxide into iron tetraoxide under an argon environment, and react with graphene and dopamine hydrochloride to form a magnetic heterostructure material of iron trioxide-graphene.
The prepared ferrotrioxide-graphene magnetic heterostructure material has good magnetic properties and thermal conductivity, and can realize the directional arrangement of fillers by applying a magnetic field to improve thermal conductivity.
Smart Images

Figure CN119551734A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a method for preparing a ferroferric oxide-graphene magnetic heterostructure material by using a calcination reduction method and an application of the material in a directional heat-conducting composite material. Background Art
[0002] Ferroferric oxide is a black crystal with magnetic properties, and graphene is a single atomic layer of carbon atom hexagonal honeycomb lattice with good electrical and thermal conductivity. The combination of the two is used to prepare the ferroferric oxide-graphene magnetic heterostructure material, which has good physical properties and has broad application prospects as a composite material.
[0003] Prior art CN109741964 A discloses an iron oxide-polydopamine-graphene composite material, its preparation method and application. However, the iron oxide in the prior art exists in the form of ferric oxide, based on the fact that "the iron oxide in the composite material is α-Fe2O3" is recorded in paragraph 0036. The iron oxide in the above prior art is non-magnetic and is mainly used on the electrode surface.
[0004] The calcination process of the present invention is carried out in an argon environment, which is a calcination reduction process, so that the iron oxide of the present invention exists in the form of Fe3O4 and has magnetism. If it is used as a filler in a thermally conductive composite material, its magnetism can be utilized to prepare a directional thermal conductive material by applying a magnetic field to directional arrange the filler.
[0005] At the same time, the preparation processes of the two are also quite different. In the prior art, iron in the form of ions participates in the reaction in the solution and is attached to graphene, while in the present invention, a complete iron oxide nanocrystal cell is first prepared, and then reacts with graphene and dopamine hydrochloride to attach to the graphene. Summary of the invention
[0006] In view of the shortcomings of the existing related technologies, the present invention provides a ferroferric oxide-graphene magnetic heterostructure material and a preparation method thereof. The ferroferric oxide unit cell is grown on the graphene surface by a calcination reduction method to present a point-surface stereoscopic structure. The material has the advantages of simple operation, good performance and low cost.
[0007] To this end, in a first aspect, the present invention provides a method for preparing a ferroferric oxide-graphene magnetic heterostructure material, comprising:
[0008] (1) Preparing ferric oxide nano-cells: slowly adding a sodium hydroxide solution to a ferric chloride solution in a water bath to prepare a ferric hydroxide gel, and sequentially drying, aging, centrifuging, washing and freeze-drying the gel to obtain ferric oxide nano-cells;
[0009] (2) Preparing ferric oxide-dopamine-graphene: adding the ferric oxide nanocrystals, graphene and dopamine hydrochloride prepared in step (1) into Tris buffer and stirring thoroughly, centrifuging, washing and freeze-drying to obtain ferric oxide-dopamine-graphene;
[0010] (3) Preparation of ferroferric oxide-graphene: The ferroferric oxide-dopamine-graphene prepared in step (2) is calcined and reduced to obtain a ferroferric oxide-graphene magnetic heterostructure material.
[0011] Furthermore, in step (1), the concentration of the ferric chloride solution is 0.03-0.05 mol / mL, preferably 0.04 mol / mL, the concentration of the sodium hydroxide solution is 0.1-0.12 mol / mL, preferably 0.108 mol / mL, the volume ratio of the two solutions is 1:1, and the water bath process for preparing the ferric hydroxide gel is heated in a water bath at 70°C-80°C, and the rate of adding the sodium hydroxide solution is between 10-20 mL / min.
[0012] Furthermore, the drying and aging in step (1) is carried out in a drying box at a drying temperature of 90-110° C. for 3-5 days.
[0013] Furthermore, in the filtering and washing process of step (1), deionized water and anhydrous ethanol are used for repeated centrifugation and washing until the supernatant is neutral, and the remaining product is collected.
[0014] Furthermore, the freeze-drying process in step (1) is carried out using a vacuum freeze dryer, wherein the freezing temperature is ≤ -55°C, preferably -60°C, and the vacuum pressure is ≤2×10 -3 Pa, preferably 1×10 -3 Pa, freeze drying time is 10-14 hours, preferably 12 hours.
[0015] Furthermore, in the mixing and stirring of step (2), the mass ratio of graphene, ferric oxide nanostructures and dopamine hydrochloride is 1:(3-5):(3-5), preferably 1:4:4; the pH of Tris buffer is 8.5, and the concentration is 1.2 mg / mL. In an embodiment of the present invention, the ratio of Tris buffer to dopamine hydrochloride is 500 mL:1 g.
[0016] Furthermore, the order and time of the mixing and stirring process in step (2) are as follows: first, the iron oxide nanocrystals and graphene are added into Tris buffer, and after being fully dispersed, dopamine hydrochloride is added, and magnetic stirring is performed in an air atmosphere for 11-13 hours, preferably 12 hours.
[0017] Furthermore, in the filtering and washing process of step (2), deionized water is used for centrifugation and washing until the supernatant is neutral, and then the remaining product is collected.
[0018] Furthermore, the freeze drying process in step (2) is performed using a vacuum freeze dryer, wherein the freezing temperature is ≤ -55°C, preferably -60°C, and the vacuum pressure is ≤2×10 -3 Pa, preferably 1×10 -3 Pa, freeze drying time is 10-14 hours, preferably 12 hours.
[0019] Furthermore, the calcination reduction process in step (3) uses a tubular furnace to calcine iron oxide-dopamine-graphene under an argon atmosphere, wherein the calcination temperature is ≥450°C, preferably 500°C, and the calcination time is 2-4 hours, preferably 3 hours.
[0020] The second aspect of the present invention provides a ferroferric oxide-graphene magnetic heterostructure material, which is obtained by the preparation method of the present invention.
[0021] The third aspect of the present invention provides the use of the ferroferric oxide-graphene magnetic heterostructure material in a directional heat conducting composite material.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) In the preparation method provided by the present invention, the high-temperature calcination process causes the polydopamine to be carbonized to form a carbon shell wrapped on the graphene surface. At the same time, the carbonized polydopamine still retains the amino functional group, so that the prepared ferroferric oxide-graphene magnetic heterostructure material exhibits good hydrophilicity and can form intermolecular hydrogen bonds with a specific substrate, effectively reducing structural defects and enhancing thermal conductivity.
[0024] (2) The carbonized dopamine continues to participate in the reduction reaction of ferric oxide as a carbon source. Finally, ferric oxide nanocrystals grow in situ on the graphene surface. A strong covalent bond is formed between the two rather than physical adsorption, which makes the prepared ferric oxide-graphene magnetic heterostructure material have a stable "point-plane" three-dimensional structure.
[0025] (3) The present invention prepares a magnetic heterostructured material of ferroferric oxide-graphene with excellent performance by means of surface modification and calcination reduction. The preparation method is simple to operate, the raw materials are readily available, the cost is low, the preparation cycle is short, the reaction conditions are mild, and it can be applied to multiple composite material technology fields.
[0026] (4) The ferroferric oxide-graphene magnetic heterostructure material prepared by the present invention has good magnetic properties and thermal conductivity. When used as a filler for a thermally conductive composite material, the filler can be oriented by applying a magnetic field or other methods, thereby greatly increasing the thermal conductivity in a certain direction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a scanning electron microscope (SEM) image of the magnetic heterostructure material prepared in Example 1.
[0029] Figure 2 This is an energy dispersive X-ray spectrometer (EDS) image of the iron element of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1.
[0030] Figure 3 This is an X-ray diffraction (XRD) image of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1.
[0031] Figure 4 This is the XPS spectrum of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1, wherein (a) is the XPS wide scan spectrum; (b) is the C 1s peak spectrum; (c) is the N 1s peak spectrum; and (d) is the Fe 2p peak spectrum.
[0032] Figure 5 This is a magnetic test of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1.
[0033] Figure 6 This is a schematic diagram of applying a rotating magnetic field during the preparation of the composite material in Example 1 to allow the magnetic heterostructure material to be oriented in polyvinyl alcohol (PVA).
[0034] Figure 7 This is a plane scanning electron microscope (SEM) image of the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1.
[0035] Figure 8 This is a cross-sectional scanning electron microscope (SEM) image of the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1.
[0036] Fig. 9 This is a Fourier transform infrared spectroscopy (FTIR) image of the ferroferric oxide-graphene / polyvinyl alcohol composite material and polyvinyl alcohol prepared in Example 1.
[0037] Fig.10 The tensile strength comparison between the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1 and polyvinyl alcohol is shown.
[0038] Fig.11 The Young's modulus comparison between the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1 and polyvinyl alcohol.
[0039] Fig.12 The thermogravimetric curves of the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1 are compared with those of polyvinyl alcohol. DETAILED DESCRIPTION
[0040] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0041] The raw materials used in the examples are all commercially available and are easily available. If industrialized, they can be scaled up in equal proportions.
[0042] Embodiment 1:
[0043] First, 2 mol of ferric chloride and 5.4 mol of sodium hydroxide were added to 50 mL of deionized water, and the mixture was stirred thoroughly to prepare ferric chloride solution and sodium hydroxide solution;
[0044] (1) under the condition of heating in a water bath at 75°C, the sodium hydroxide solution was added dropwise to the ferric chloride solution within 5 minutes, and the solution was stirred continuously at the same temperature for 5 minutes to obtain ferric hydroxide gel; the ferric hydroxide gel was placed in a drying oven at 100°C for natural aging for 4 days, and the solution was repeatedly centrifuged and washed with deionized water and anhydrous ethanol until the supernatant was neutral, and the remaining product was collected and freeze-dried for 12 hours to obtain ferric oxide nanocrystals;
[0045] (2) Add 2 g of iron oxide nanocrystals and 0.5 g of graphene into 250 mL of Tris buffer (1.2 mg / mL, pH = 8.5), add 2 g of dopamine hydrochloride after fully dispersing, and stir magnetically for 12 hours in an air atmosphere; centrifuge the mixed solution with deionized water, wash until the supernatant is neutral, and collect the remaining product and freeze-dry it for 12 hours;
[0046] (3) The product of step (2) was placed in a tubular furnace and calcined at 500° C. for 3 hours under an argon atmosphere to obtain a powder sample of a ferroferric oxide-graphene magnetic heterostructure material.
[0047] Figure 1 This is a scanning electron microscope (SEM) image of the magnetic heterostructure material prepared in Example 1. It can be seen that the ferroferric oxide-graphene heterostructure material is a "point-plane" type three-dimensional structure, and a large number of nano-scale unit cells are attached to the graphene surface.
[0048] Figure 2This is an energy dispersive X-ray spectrometer (EDS) image of the iron element of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1. It can be seen that the unit cell is mainly composed of iron element.
[0049] Figure 3 This is the X-ray diffraction (XRD) image of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1. It can be seen that the ferroferric oxide-graphene magnetic heterostructure material has a characteristic peak at 2θ=26.68°, corresponding to the characteristic diffraction peak of the (002) crystal plane of graphene; there are characteristic diffraction peaks at 2θ=18.38°, 30.26°, 35.53°, 37.16°, 43.28°, 53.58°, 57.01°, 62.63° and 74.22°, corresponding to the characteristic diffraction peaks of the (111), (220), (311), (222), (400), (422), (511), (440) and (530) crystal planes of ferroferric oxide, respectively. Combining the SEM image results and the preparation process, it can be seen that the ferroferric oxide-graphene magnetic heterostructure material maintains the lattice structure of graphene and grows ferroferric oxide nanocells in situ on the graphene surface.
[0050] Figure 4 (a) XPS wide scan spectrum of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1; (b) C 1s peak spectrum; (c) N 1s peak spectrum; (d) Fe 2p peak spectrum. Figure 4 (a) It can be seen that the Fe 2p characteristic peak appears in the XPS wide scan spectrum of the ferroferric oxide-graphene magnetic heterostructure material, and the atomic content of Fe is about 4.53%. The peak spectra of C 1s, N 1s and Fe 2p of the ferroferric oxide-graphene magnetic heterostructure material are further analyzed. Figure 4 (b) is the C 1s spectrum of the ferroferric oxide-graphene magnetic heterostructure material. After peak fitting, fitting peaks of CC bond (284.8 eV), CN bond (285.4 eV) and C-OH bond (286.7 eV) appeared. Figure 4 (c) is the N 1s spectrum of the ferroferric oxide-graphene magnetic heterostructure material. After peak fitting, fitting peaks of -NH- bond (398.6 eV) and -NH2 bond (400.4 eV) appeared, indicating that the surface of the ferroferric oxide-graphene magnetic heterostructure material still contains a large number of amino functional groups. Figure 4 (d) is the Fe 2p characteristic peak of the ferroferric oxide-graphene magnetic heterostructure material. After peak fitting, the peaks are consistent with the Fe 3+The characteristic Fe 2p3 / 2 (711.1 eV), Fe 2p1 / 2 (724.1 eV) fitting peaks and satellite peaks Fe 2p3 / 2 (714.6 eV), Fe2p1 / 2 (727.9 eV) are consistent with the Fe 2+ The characteristic fitting peaks of Fe 2p3 / 2 (709.7eV) and Fe 2p1 / 2 (722.6eV) are consistent with the XPS spectrum characteristics of ferroferric oxide, indicating that ferroferric oxide grows in situ on the graphene surface. Combined with the preparation process analysis of ferroferric oxide-graphene magnetic heterostructure materials, it can be seen that the dopamine modified layer is carbonized at a high temperature of 500°C to form a carbon shell wrapped around the ferric oxide unit cell and the graphene surface, and participates in the reduction reaction of ferric oxide as a carbon source. At this temperature, ferric oxide is reduced to ferroferric oxide particles attached to the graphene surface, and finally ferroferric oxide-graphene magnetic heterostructure materials are obtained.
[0051] Figure 5 The magnetic properties of the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1 are as follows: Figure 5 (a) It can be seen that the ferroferric oxide-graphene aqueous solution becomes clear and transparent in a short time, and the ferroferric oxide-graphene samples in the solution are all gathered on one side of the magnet; Figure 5 As shown in (b), another appropriate amount of ferroferric oxide-graphene sample is placed in a microcentrifuge tube. When the centrifuge tube is close to the magnet, the ferroferric oxide-graphene sample is all gathered on one side of the magnet, so that the centrifuge tube is adsorbed on the surface of the magnet. These phenomena indicate that the ferroferric oxide-graphene magnetic heterostructure material has very excellent magnetic properties.
[0052] The ferroferric oxide-graphene magnetic heterostructure material prepared in Example 1 was added to polyvinyl alcohol (PVA) to prepare a ferroferric oxide-graphene / polyvinyl alcohol composite material, and thermal and mechanical properties tests were performed. The specific steps are as follows:
[0053] (1) Take an appropriate amount of polyvinyl alcohol and heat it to dissolve it in deionized water to prepare a polyvinyl alcohol aqueous solution as the base material of the filler;
[0054] (2) After ultrasonically dispersing the ferroferric oxide-graphene magnetic heterostructure material in an appropriate amount of deionized water, the solution was fully mixed with a polyvinyl alcohol aqueous solution to obtain a ferroferric oxide-graphene / polyvinyl alcohol mixed solution, which was poured into a mold so that the mass fraction of the ferroferric oxide-graphene magnetic heterostructure material was 5wt%;
[0055] (3) Place the electric turntable between two strong magnets, and place the mold at the center of the turntable. Apply a rotating magnetic field and adjust the turntable speed to 2 r / min. The sample is naturally gelled in the rotating magnetic field at room temperature for 12 hours and then taken out.
[0056] (4) The film is dried naturally at room temperature to obtain a FeO-graphene / polyvinyl alcohol composite material.
[0057] The ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in this embodiment has a directional thermal conductivity of 8.22 W·m -1 ·K -1 , which is higher than the thermal conductivity of polyvinyl alcohol (0.6 W·m -1 ·K -1 ) increased by 1270%; vertical thermal conductivity reached 0.5W·m -1 ·K -1 , compared with the vertical thermal conductivity of polyvinyl alcohol (0.4 W·m -1 ·K -1 ) increased by 25%.
[0058] Figure 6 The figure is a schematic diagram of applying a rotating magnetic field to the material in Example 1. Specifically, in step (3), the ferroferric oxide-graphene / polyvinyl alcohol mixed solution contained in the mold is placed in an electric turntable, and opposite magnets are placed on both sides of the electric turntable to form a fixed magnetic field. The electric turntable is rotated to form a relative rotating magnetic field, and the material is taken out after being naturally gelled for 12 hours. Then, step (4) is performed.
[0059] Figure 7 This is a planar scanning electron microscope (SEM) image of the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1. It can be seen that the surface of the material is relatively flat without obvious structural defects, indicating that the filler is well dispersed in the substrate.
[0060] Figure 8 This is a cross-sectional scanning electron microscope (SEM) image of the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 1. It can be seen that the ferroferric oxide-graphene magnetic heterostructure material is tightly attached to the substrate, and there are no obvious structural defects inside the composite material. This is because the surface of ferroferric oxide-graphene contains hydroxyl and amino functional groups, which can form a hydrogen bond network with the hydroxyl groups on the surface of polyvinyl alcohol, thereby enhancing the interface between ferroferric oxide-graphene and polyvinyl alcohol. In addition, the ferroferric oxide-graphene is neatly arranged along the plane direction, which is consistent with the direction of the rotating magnetic field applied in the experiment.
[0061] Fig. 9 This is the Fourier transform infrared spectroscopy (FTIR) image of the ferroferric oxide-graphene / polyvinyl alcohol composite material and polyvinyl alcohol prepared in Example 1. The ferroferric oxide-graphene / polyvinyl alcohol composite material has a wavelength of 833 cm -1The NH characteristic peak appears at the position, proving that FeO-graphene contains amino groups. Compared with the polyvinyl alcohol material, the center position of the characteristic peak of hydrogen bonding between molecules of FeO-graphene / polyvinyl alcohol composite material is 3337cm -1 Move to 3291cm -1 The results of SEM analysis of the FeO-graphene / PVA composite material show that the hydroxyl and amino groups on the surface of the FeO-graphene heterogeneous filler can form intermolecular hydrogen bonds with the PVA, allowing the FeO-graphene to be tightly integrated with the PVA. Therefore, there are no obvious structural defects on the surface and inside of the FeO-graphene / PVA composite material.
[0062] Fig.10 The tensile strength comparison between the ferroferric oxide-graphene / polyvinyl alcohol composite material and polyvinyl alcohol prepared in Example 1. It can be seen that the ferroferric oxide-graphene / polyvinyl alcohol composite material has a stronger tensile strength than polyvinyl alcohol.
[0063] Fig.11 The Young's modulus comparison between the ferroferric oxide-graphene / polyvinyl alcohol composite material and polyvinyl alcohol prepared in Example 1. It can be seen that the ferroferric oxide-graphene / polyvinyl alcohol composite material has a very outstanding Young's modulus compared with polyvinyl alcohol.
[0064] Fig.12 The thermogravimetric curves of the ferroferric oxide-graphene / polyvinyl alcohol composite material and polyvinyl alcohol prepared in Example 1 are compared. It can be seen that the ferroferric oxide-graphene / polyvinyl alcohol composite material has good thermal stability, and the change trend of the thermogravimetric curve of polyvinyl alcohol is basically consistent, but the temperature at which the weight of the ferroferric oxide-graphene / polyvinyl alcohol composite material tends to be stable is higher than that of polyvinyl alcohol.
[0065] Example 2
[0066] First, 4 mol of ferric chloride and 11 mol of sodium hydroxide were added to 100 mL of deionized water, and the mixture was stirred thoroughly to prepare ferric chloride solution and sodium hydroxide solution;
[0067] (1) under the condition of heating at 80°C in a water bath, the sodium hydroxide solution was added dropwise to the ferric chloride solution within 10 minutes, and the solution was stirred continuously at the same temperature for 10 minutes to obtain ferric hydroxide gel; the ferric hydroxide gel was placed in a drying oven at 100°C for natural aging for 4 days, and the solution was repeatedly centrifuged and washed with deionized water and anhydrous ethanol until the supernatant was neutral, and the remaining product was collected and freeze-dried for 12 hours to obtain ferric oxide nanocrystals;
[0068] (2) 4 g of iron oxide nanocrystals and 1 g of graphene were added to 500 mL of Tris buffer (1.2 mg / mL, pH = 8.5). After being fully dispersed, 4 g of dopamine hydrochloride was added and magnetically stirred for 13 hours in an air atmosphere. The mixed solution was centrifuged and washed with deionized water until the supernatant was neutral, and the remaining product was collected and freeze-dried for 14 hours.
[0069] (3) The product of step (2) was placed in a tubular furnace and calcined at 460° C. for 4 hours under an argon atmosphere to obtain a powder sample of a ferroferric oxide-graphene magnetic heterostructure material.
[0070] In the same manner as in Example 1, the ferroferric oxide-graphene magnetic heterostructure material prepared in Example 2 was dispersed in a polyvinyl alcohol aqueous solution and a magnetic field was applied to prepare a ferroferric oxide-graphene / polyvinyl alcohol composite material.
[0071] According to the test results, the ferroferric oxide-graphene / polyvinyl alcohol composite material prepared in Example 2 has a tensile strength of 43.27 MPa, a Young's modulus of 2.59 GPa, and a directional thermal conductivity of 8.17 W·m -1 ·K -1 , vertical thermal conductivity is 0.5 W·m -1 ·K -1 .
[0072] Comparative Example 1
[0073] The preparation process of the heterogeneous structure material is the same as that of Example 1, except that the tubular furnace calcination atmosphere in step (3) is air. Figure 5 In the magnetic test shown, the material was placed in a transparent centrifuge tube, dispersed with water and placed close to a magnet. The liquid in the centrifuge tube did not change significantly. Therefore, it can be shown that calcination in an air atmosphere cannot fully reduce the iron oxide unit cell, and the resulting heterostructure material has no magnetism.
[0074] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing ferroferric oxide-graphene magnetic heterostructure material, characterized in that: The following steps are involved: (1) Preparing ferric oxide nano-cells: slowly adding a sodium hydroxide solution to a ferric chloride solution in a water bath to prepare a ferric hydroxide gel, and sequentially drying, aging, centrifuging, washing and freeze-drying the gel to obtain ferric oxide nano-cells; (2) Preparing ferric oxide-dopamine-graphene: adding the ferric oxide nanocrystals, graphene and dopamine hydrochloride prepared in step (1) into Tris buffer and stirring thoroughly, centrifuging, washing and freeze-drying to obtain ferric oxide-dopamine-graphene; (3) Preparation of ferroferric oxide-graphene: The ferroferric oxide-dopamine-graphene prepared in step (2) is calcined and reduced to obtain a ferroferric oxide-graphene magnetic heterostructure material.
2. The method according to claim 1, characterized in that In step (1), the concentration of the ferric chloride solution is 0.03-0.05 mol / mL, the concentration of the sodium hydroxide solution is 0.1-0.12 mol / mL, and the volume ratio of the two solutions is 1:1; the water bath process for preparing the ferric hydroxide gel adopts a water bath heating at 70°C-80°C, and the speed of adding the sodium hydroxide solution is between 10-20 mL / min.
3. The method according to claim 1, characterized in that The drying and aging in step (1) is carried out in a drying oven at a temperature of 90-110° C. for 3-5 days; And / or, the centrifugation and washing process in step (1) is repeated centrifugation and washing with deionized water and anhydrous ethanol until the supernatant is neutral, and the remaining product is collected; And / or, the freeze drying process in step (1) is carried out using a vacuum freeze dryer, wherein the freezing temperature is ≤-55°C and the vacuum pressure is ≤2×10 -3 Pa, freeze drying time is 10-14 hours.
4. The method according to claim 1, characterized in that: In the mixing and stirring of step (2), the mass ratio of graphene, ferric oxide nanocrystals and dopamine hydrochloride is 1:(3-5):(3-5); the pH of Tris buffer is 8.5, and the concentration is 1.2 mg / mL.
5. The method according to claim 1, characterized in that The order and time of the mixing and stirring process in step (2) are as follows: first, add the iron oxide nanocrystals and graphene together into Tris buffer, add dopamine hydrochloride after they are fully dispersed, and stir magnetically for 11-13 hours in an air atmosphere.
6. The method according to claim 1, characterized in that The filtering and washing process in step (2) is to centrifuge with deionized water, wash until the supernatant is neutral, and collect the remaining product; And / or, the freeze drying process in step (2) is performed by using a vacuum freeze dryer, wherein the freezing temperature is ≤-55°C and the vacuum pressure is ≤2×10 -3 Pa, freeze drying time is 10-14 hours.
7. The method according to claim 1, characterized in that The calcination reduction process in step (3) uses a tubular furnace to calcine iron oxide-dopamine-graphene under an argon atmosphere, wherein the calcination temperature is ≥450° C. and the calcination time is 2-4 hours.
8. The method according to claim 7, characterized in that The calcination temperature in step (3) is 500° C. and the calcination time is 3 hours.
9. The ferroferric oxide-graphene magnetic heterostructure material prepared by the method according to any one of claims 1 to 8.
10. Use of the ferroferric oxide-graphene magnetic heterostructure material according to claim 9 in a directional heat conducting composite material.
Citation Information
Patent Citations
Preparation method of magnetic graphene aerogel
CN107140620A
Preparation method of Fe3O4 / nitrogen-doped graphene material capable of being used for lithium ion battery negative electrode
CN107910515A
A preparation method for a self-supporting high-sulfur loaded cathode material for lithium-sulfur battery
CN109244455A
Ferric oxide-polydopamine-graphene composite material, preparation method and application thereof
CN109741964A
Carbon-coated ferroferric oxide lithium ion battery negative electrode material and preparation method thereof
CN117985769A